A Black-Box Method for Parametric Model Order Reduction. Issue 1 (2015) - Geuss, M.; Lohmann, B.; Peherstorfer, B.; Willcox, K.
Abstract: A black-box method for parametric model order reduction is presented that includes method selection, model refinement and error prediction using a cross-validation-based error indicator. The method is demonstrated for the interpolation of reduced system matrices.